European legal methodology - Riesenhuber, Karl (Ius communitatis series, 2017)
EU law is an autonomous legal system. It requires its own methodology, independent of the national traditions of the Member States. The contributions to this volume provide elements of a genuinely European legal method. They discuss the foundations of European legal methodology in Roman law and in the development of national legal methods in the 19th century as well as the economic and comparative background. Core issues of legal methods such as the sources of law, the interpretation of EU primary law and secondary legislation, the concretisation of general clauses, and judicial development of the law are also analysed. Furthermore, the temporal effects of EU directives on the one hand and of judgments of the Court of Justice of the European Union raise specific issues of EU law. Contributions are also devoted to issues of a multi-level legal system. Beyond general aspects, directives, in particular, raise special questions: what is their impact on the interpretation of national law; and what are the methodological consequences of a transposition of directives beyond their original scope ('gold-plating')? Further contributions inquire into methodological issues in contract law, employment law, company law, capital market law and competition law. They illustrate the general aspects of European legal methods with a view to specific applications and also reveal specific issues of methods which occur in these areas. Finally, legal methods from national perspectives of different Member States, namely France, Germany, Italy, Poland, Spain and the United Kingdom, are examined. The authors reveal national traditions of legal methods and national preconceptions and illustrate the application of EU legal methods in different national contexts
Auch als NUR ; 820 gezählt
Keywords: Juristische Methodik; Europäische Union